Solving Transportation and Travelling Salesman Problems in Excel Environment - Stoilova, Krasimira; Stoilov, Todor (Advanced Aspects of Engineering Research Vol. 15, 2021)
The urban traffic in city areas leads to serious problems with traffic jams, air and noise pollution, social problems, etc. The chapter presents solutions of two important transportation problems: distribution of goods and travelling salesman problems, applied in an urban area. The solutions of such problems lead to improvement of the management of the transportation services. The distribution problem is formalized by mixed integer-linear programming problem. The Travelling Salesman Problem (TSP) has long history for the design of appropriate numerical algorithms for its solution. It belongs to a class of combinatorial optimization problems, which insist considerable computational workload for its solution. The added value of the research is that it gives examples how these two problems can be solved by wide available software suit. Real transportation problems in Sofia city are defined. It is illustrated how these problems can be solved relatively easy in Excel environment. Appropriate programming of the Excel sheet and its software application Solver is given. This work provides examples for the definition of transportation problem for distribution of goods and TSP one and their solutions.